Is the Child Health / Family Income Gradient Universal? : Evidence from England - Alison Currie; Michael A. Shields; Stephen Wheatley Price (Institute for the Study of Labor (IZA), 2004)
In an influential study Case et al. (2002) documented a positive relationship between family income and child health in the US, with the slope of the gradient being larger for older than younger children. In this paper we explore the child health income gradient in England, which has a comprehensive publicly-funded National Health Service (NHS) founded on the twin principles of health care being free at the point of delivery and equality of access for the whole population. Our analysis is based on a sample of over 13,000 children (and their parents) drawn from the Health Survey for England. In accordance with Case et al. (2002), we find consistent and robust evidence of a significant family income gradient in child health using the subjective general health status measure. However, in England the size of the gradient is considerably smaller than that found for the US and we find no evidence that its slope increases with child age. We also provide new evidence that nutrition and family lifestyle choices have an important role in determining child health and that child health outcomes are highly correlated within the family. In addition, we find no evidence of an income gradient for objective indicators of child health, derived from nurse measurements and blood test results. Together our evidence is consistent with the hypothesis that the NHS has a protective effect on the health of children in England.
Keywords: I1; 330; child health; income gradient; chronic illness; nutrition; lifestyle; Kinder; Gesundheit; Haushaltseinkommen; Ernährung; Lifestyle; Schätzung; Grossbritannien